Upaya Meningkatkan Perkembangan Kognitif menggunakan Metode Bermain Berbantuan Media Menara Angka - Luh Srinadi; Kadek Suartini; Putu Adi Kristiani; Maria Yustina Nggera Ngaba (Early Childhood Education Development and Studies (ECEDS), 2021)
The issues contained in the study on cognitive development in low numbers recognition capabilities.The purpose of this research was to study the improvement within cognitive development in the introduction of numbers after the application of the playing method using the number tower media to the B3 group children during the second semester or the academic year 2020/2021in TK-SD Satu Atap Negeri 1 Kenderan. This type of study is a classroom action-based research which was carried out in two cycles with 13 children as the subjects during the second semester or the academic 2020/2021. The data on the cognitive development in the introduction of numbers were collected by observation method with observation forms as the instrument. The data in this study were analyzed using descriptive statistical analysis method and quantitative descriptive analysis method. The result of the data analysis shows that there was 70,75% improvement for the cognitive development in the introduction of numbers with the application of the playing method in the first cycle, which can be categorized as average.